Current Status of the Industrial Use of Linear Programming - Smith, L. Wheaton (Management Science, 1956)
The 1955 Conference on Business Statistics (Held in Philadelphia, June 9 and 10, 1955, sponsored by the Wharton School of the University of Pennsylvania, and by the American Statistical Association. The panel on linear programming was organised by M. M. Flood.) included a two-day panel discussion on “The Current Uses of Linear Programming in American Business.” The participants in the panel represented a wide enough segment of those who have been active in linear programming to permit brief coverage of a major portion of the active applications. Consequently, this report attempts to summarize the “state of the art” on the basis of that conference (The report is based in part on a verbal summary at the close of the panel discussions by a committee which consisted of A. Orden, L. Wheaton Smith, Jr., and H. H. Cauvet.).